Controlled-release experiment to investigate uncertainties in UAV-based emission quantification for methane point sources - Morales, Randulph; Ravelid, Jonas; Vinkovic, Katarina; Korbeń, Piotr; Tuzson, Béla; Emmenegger, Lukas; Chen, Huilin; Schmidt, Martina; Humbel, Sebastian; Brunner, Dominik (Atmospheric measurement techniques, 2022)
Abstract: Mapping trace gas emission plumes using in situ measurements from unmanned aerial vehicles (UAVs) is an emerging and attractive possibility to quantify emissions from localized sources. Here, we present the results of an extensive controlled-release experiment in Dübendorf, Switzerland, which was conducted to develop an optimal quantification method and to determine the related uncertainties under various environmental and sampling conditions. Atmospheric methane mole fractions were simultaneously measured using a miniaturized fast-response quantum cascade laser absorption spectrometer (QCLAS) and an active AirCore system mounted on a commercial UAV. Emission fluxes were estimated using a mass-balance method by flying the UAV-based system through a vertical cross-section downwind of the point source perpendicular to the main wind direction at multiple altitudes. A refined kriging framework, called cluster-based kriging, was developed to spatially map individual methane measurement points into the whole measurement plane, while taking into account the different spatial scales between background and enhanced methane values in the plume. We found that the new kriging framework resulted in better quantification compared to ordinary kriging...